2022
DOI: 10.3389/fnins.2022.866722
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Combined Exposure to Nicotine and Tetrahydrocannabinol via Electronic Cigarettes in Pregnant Rats

Abstract: Nicotine and cannabis are two of the most commonly consumed licit and illicit drugs during pregnancy, often consumed together via e-cigarettes. Vaping is assumed to be a safer alternative than traditional routes of consumption, yet the potential consequences of prenatal e-cigarette exposure are largely unknown, particularly when these two drugs are co-consumed. In a novel co-exposure model, pregnant Sprague-Dawley rats received nicotine (36 mg/mL), tetrahydrocannabinol (THC) (100 mg/mL), the combination, or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 85 publications
2
6
0
Order By: Relevance
“…Although some group differences in nicotine and cotinine were confirmed, there were only minor sex and strain differences in terms of mean concentrations of either cotinine or nicotine. The nicotine and cotinine levels were also similar to levels reported for male Wistar rats exposed to vapor from a 40 mg/mL nicotine concentration over 60 minutes using slightly different puffing parameters (Montanari et al, 2020) but were higher than those reported for pregnant rats exposed to nicotine (36 mg/mL) vapor using different puffing parameters for 30 minutes (Breit et al, 2022). The cotinine levels were also similar to those reported in a mouse model of vapor inhalation (Cooper et al, 2021).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Although some group differences in nicotine and cotinine were confirmed, there were only minor sex and strain differences in terms of mean concentrations of either cotinine or nicotine. The nicotine and cotinine levels were also similar to levels reported for male Wistar rats exposed to vapor from a 40 mg/mL nicotine concentration over 60 minutes using slightly different puffing parameters (Montanari et al, 2020) but were higher than those reported for pregnant rats exposed to nicotine (36 mg/mL) vapor using different puffing parameters for 30 minutes (Breit et al, 2022). The cotinine levels were also similar to those reported in a mouse model of vapor inhalation (Cooper et al, 2021).…”
Section: Discussionsupporting
confidence: 75%
“…The goal of this study was therefore to determine if there are any lasting consequences of repeated vapor inhalation of nicotine in adolescent rats. For this, we used an ENDS-based system that has been previously shown effective in delivering active nicotine doses to adult rats of either sex (Javadi-Paydar et al, 2019b; Lallai et al, 2021; Montanari et al, 2020), to pregnant rats (Breit et al, 2022) and to mice (Cooper et al, 2021; Echeveste Sanchez et al, 2022; Henderson and Cooper, 2021). ENDS-based systems have shown efficacy for nicotine self-administration in rats (Smith et al, 2020) and mice (Cooper et al, 2021; Henderson and Cooper, 2021) and repeated daily exposure to nicotine via ENDS vapor inhalation leads to withdrawal following discontinuation in adult rats (Montanari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As one minor caveat, one recent report suggest that vaping nicotine and THC together leads to lower plasma drug levels than when the same concentration of either drug is vaped alone (Breit et al, 2022). However given that the magnitude of tolerance to hypothermic effects of THC was similar across the THC-only and THC-Nicotine groups, and similar to our prior report (Nguyen et al, 2016b), this seems unlikely to have occurred in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this study was to determine any lasting impact of repeated vapor inhalation of nicotine and THC in adolescent rats on the effects of nicotine and heroin in adulthood. For this, we used an EDDS-based system that has been previously shown effective in delivering nicotine to adult rats (Javadi-Paydar et al, 2019b; Lallai et al, 2021; Montanari et al, 2020), adolescent rats (Gutierrez et al, 2022) and to rat pups in utero (Breit et al, 2022; Hussain, Breit and Thomas, 2022). EDDS-based systems have shown efficacy for nicotine self-administration in rats (Lallai et al, 2021; Smith et al, 2020) and mice (Cooper, Akers and Henderson, 2021; Henderson and Cooper, 2021), and have been used to show that repeated daily exposure to nicotine vapor leads to significant withdrawal following discontinuation in adult rats (Montanari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Systematically designed dosage and exposure regimens, including studies that continue exposure postnatally to capture the full rodent equivalent to prenatal human development. There should also be an increased effort to use exposure routes that have similar pharmacokinetics to smoking such as vapour exposures (Frie et al, 2020;Breit et al, 2022). Preclinical cognitive findings are summarised below in Table 1.…”
Section: Preclinicalmentioning
confidence: 99%